Memutus Siklus: Bagaimana Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, Upah Minimum Regional, Dan Indeks Harapan Hidup Berdampak Pada Tingkat Kemiskinan - Almuttaqin, Muhammad Akbar; Rosyadi, M. Irfan; M. Nur, Nuriman (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine the effects of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), Regional Minimum Wage (MW), and Life Expectancy Index (LEI) on poverty levels in Bengkalis Regency. The object of this study is Bengkalis Regency, one of the regencies in Riau Province. This research utilizes panel data over a 10-year period from 2013 to 2023, obtained from the publications of the Bengkalis Regency Statistics Agency (BPS). The data analysis tool employed is the Ordinary Least Squares (OLS) model with the assistance of Eviews 12 software. The results indicate that the Human Development Index and Life Expectancy Index significantly affect poverty levels in Bengkalis Regency, whereas Gross Regional Domestic Product and Regional Minimum Wage do not have a significant impact on poverty levels in the regency.